PERSETUJUAN PEMBIMBING PENGARUH PEMANFAATAN MADU DAN AIR PERASAN JERUK NIPIS TERHADAP PENYEMBUHAN JERAWAT - mayuna, novia elsa; rahmiati, rahmiati; yuliana, yuliana (Journal of Home Economics and Tourism, 2013)
This study aimed to analyze the healing acne with honey and lemon ofwater juice are assessed from indicators of color, shape, volume andamount of acne. Type of study is a quasi experimental design withnonequivalent control group. This study population is a student ofUNP has acne papulopustul type. Sampling technique used purposivesampling by voolunter with a sample of 12 people. The data collectedin this study is primary data. The technique of data analysis usingANOVA and Duncan test. The results that there is a significant effectthe use of honey and lemon of water juice to healing acne. Testingcontinued with Duncan test showed a significant difference from thefour different treatments, can be seen from the indicator color, shape,volume and amount of acne with the best used to the group lemon ofwater juice (X3) and the group lemon of water juice + honey (X4)onces in the six days.Kata Kunci: madu, air perasan jeruk nipis, jerawat